Penanganan Regimen Terapeutik Inefektif Pada Anak Dengan Tuberkulosis - Pratiwi, Linda Kurniawati; , Endang Zulaicha Susilaningsih, S.Kp.,M.Kep (2017)
: the proportion of TB cases among children in new cases pulmonary tuberculosis were recorded in Central Java in 2015 amounted to 7,51%,increase compared propped child tuberculosis in 2014 6,63%. Pulmonary tuberculosis is an infectious disease that attacks the lungs caused parenting by Mycobacterium Tuberculosis.The most important thing in the treatment of tuberculosis something regularity of taking medicine. There is a problem in the irregularity in taking drugs that led to five effects of drug withdrawal. There is a problem in drug retention that can prolong the treatment process, can cause complications and cause bacterial immunity to the drugs consumed. Purpose: the general purpose able to describe the handling of therapeutic regimens. A special purpose of analyzing the assessment of ineffective therapeutic regimens, analyzing the interventions involved in the treatment effort of ineffective therapeutic regimens, analyzing the actions taken in handling the therapeutic regimen in children with TBC, analyzing medication adherence before and after the implementation. Methods: the author usesa descriptive method with willing cases for 6 days in Sukoharjo. Result: after the act of games for therapy, providing health education, motivation, giving daily medication calendars and giving praise and rewards, for 3 day patient taking medication into a regular irregularly in taking medicine and make a return visit to monitor the calendar medication. Conclution: for handling that children do not get bored of taking drugs of tuberculosis given the action of games for therapy, providing health education, motivation, giving daily medication calendars and giving praise and rewards.